W poszukiwaniu uwarunkowań transmisji międzypokoleniowej - znaczenie pełnionej roli rodzinnej w kontynuowaniu wzorców rodzicielstwa = The search for intergenerational transmission' determinants - the impact of one's family role on continuing patterns of parenting - Farnicka, Marzanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The goal of the study was the search for similarity between generations in respect of social knowledge and expected experience connected with parenthood. In the research model, the following variables were distinguished: he concept of normative development in three generations, the sense of influence on one's own life and expectations towards future related to the time of realization of parenthood.
Keywords: transmisja międzypokoleniowa; wczesna dorosłość; podejmowanie rodzicielstwa; relacje trójpokoleniowe; developmental task; parenthood; changes in family life patterns; intergeneration transmission; young adult